Influence of line management on public servants’ motivation - Aliyev, Emirkhan; Assylbekova, Aidana; Bizhanov, Chingiz (Nazarbayev University Graduate School of Public Policy, 2019)
Line management practices are paid a vast amount of attention in the private sector and in international organizations in many countries, as it has a strong impact on employees’ motivation. Whether line management is also important in motivating public servants in Kazakhstan? The research team conducted a survey of the private and public sector employees to answer this question. The research was focused on line management practices and their influence on employees’ motivation in both sectors. As the results of the research showed, there is a strong correlation between line management practices and employees’ motivation and at the same time, there are differences in those practices between public and private sector, with private sector international companies being more effective in terms of line management. By outlining purposes or stating the nature of the present research the qualitative data analysis was used in this project...
Keywords: line management; management